Early marine migration of European silver eel(Anguilla anguilla) in Northern Norway - Davidsen, Jan Grimsrud; Rikardsen, Audun H.; Finstad, B; Økland, Finn; Thorstad, E.B.; Mo, TA (Journal of Fish Biology, 2011)
This is the accepted manuscript version of the article. Published article available at http://dx.doi.org/10.1111/j.1095-8649.2011.02943.x